2004
DOI: 10.2337/diacare.27.4.914
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Clinical Factors Associated With Depression Among Individuals With Diabetes

Abstract: OBJECTIVE -The goal of this study was to determine the behavioral and clinical characteristics of diabetes that are associated with depression after controlling for potentially confounding variables. RESEARCH DESIGN AND METHODS-A population-based mail survey was sent to patients with diabetes from nine primary care clinics of a health maintenance organization. The Patient Health Questionnaire was used to diagnose depression, and automated diagnostic, pharmacy, and laboratory data were used to measure diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
299
8
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 390 publications
(359 citation statements)
references
References 39 publications
44
299
8
8
Order By: Relevance
“…The characteristics of our depressed patients were consistent with reports from other studies where depression was more common in females [30,31] and was associated with physical inactivity [4] and diabetic complications [7]. We also found that depressed patients had worse lipid profiles.…”
Section: Discussionsupporting
confidence: 91%
“…The characteristics of our depressed patients were consistent with reports from other studies where depression was more common in females [30,31] and was associated with physical inactivity [4] and diabetic complications [7]. We also found that depressed patients had worse lipid profiles.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is particularly important because patients with diabetes are at a higher risk for depression compared to the general population [60][61][62] and depression further complicates diabetes self-care. 61,63 We hypothesize that patient self-blame for difficulty achieving treatment goals may lead to or exacerbate distress and/or depressive symptoms. This hypothesis needs to be tested with more refined quantitative measures in patients with different ethnic, cultural or socioeconomic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Depression may add to the risk of dementia associated with diabetes in several ways. Comorbid depression in patients with diabetes is associated with poor glucose control 33 , higher BMI 34 , higher rates of smoking 34 , physical inactivity, and lapses in adherence to hypoglycemic, lipid-lowing, and antihypertensive medications 17 . These adverse self-care characteristics could increase risk of macrovascular and microvascular complications.…”
Section: Discussionmentioning
confidence: 99%